Beyond Curriculum Reform: The Influence of Integration on Communication and Presentation Skills in Medical Students: A Mixed-Method Study - Sharif AF; Moustafa NM; Abdo SA; Aloshari SHA; Al-Dress A (Advances in Medical Education and Practice, 2025)
Asmaa F Sharif,1,2 Nouran M Moustafa,3,4 Sanaa A Abdo,5 Samar HA Aloshari,6 Abdulmajeed Al-Dress7,8 1Clinical Medical Sciences Department, College of Medicine, Dar Al Uloom University, Riyadh, Saudi Arabia; 2Forensic Medicine and Clinical Toxicology Department, Faculty of Medicine, Tanta University, Tanta, Egypt; 3Medical Education Department, College of Medicine, Dar Al Uloom University, Riyadh, Saudi Arabia; 4Medical Microbiology & Immunology Department, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 5Public Health and Community Medicine Department, Faculty of Medicine, Tanta University, Tanta, Egypt; 6Department of Public Health and Community Medicine, Faculty of Medicine, Taiz University, Taiz, Yemen; 7Departments of Physiology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 8College of Medicine, Dar Al Uloom University, Riyadh, Saudi ArabiaCorrespondence: Samar HA Aloshari, Department of Public Health and Community Medicine, Faculty of Medicine, Taiz University, P.O. Box 6803, Taiz, Yemen, Tel +9674232429, Email dr.alosharisamar@gmail.comPurpose: The present study aimed to explore the current presentation and communication practices among medical students and investigate the influence of adopting an integrated curriculum on communication and presentation skills in different phases, emphasizing the motivating and challenging aspects.Methods: An exploratory mixed-methods two-phase study was conducted among 362 medical students at different phases of the program.Results: The current study conveyed a comparable positive self-perception of the current presentation designs and styles among medical students. More than 72% and 53% of students thought problem and case-based learning positively influenced their communication and presentation skills, respectively. Interns were more likely to identify themselves as storytellers than students in earlier years (7.9/10). Most students (> 80%) reported positive perceptions of their pronunciation, tone, volume, and fluency. There was a positive correlation between presentation and communication skills (r=0.534, p=0.000). Approximately 37% of students agreed that problem-based learning and case-based learning improved their presentation and communication skills. The primary reported challenges were the time constraints (40.1%), and the need for more training (34%) and practice (39.2%). Other reported challenges were the high stress levels and complex adaptation to audience expectations. The most motivating factors were the interest in improvement (66.3%), willing to increase self-confidence (64.9%), obtaining high grades (53.3%), and being more efficient (52.5%). Other motivations were exposure to real-world scenarios and the presence of role models. However, while students agreed that their skills are improving, this progress feels slow. Though clinical phase students showed higher achievement of several learning outcomes than younger students, basic science-phase students outperformed their clinical phase counterparts in recognizing the importance of teamwork (93.25% versus 91.16%).Conclusion: The integrated curriculum offers equal opportunities to enhance communication and presentation skills in all phases of the program. Addressing the reported challenges and fostering the motivating factors are advisable.Keywords: curriculum, communication, motivation, learning outcomes, doctor-patient relationship, innovative strategies